STRATEGI PENINGKATAN PROFESIONALISME DAN KOMPETENSI APARATUR SIPIL NEGARA (ASN) PADA JABATAN FUNGSIONAL ANALIS KEPEGAWAIAN - Saifudin Saifudin (Journal of Social and Political Science)
Increasing the competence and professionalism of personnel analysts is needed so that the implementation of personnel management services at the University of Jember can be guaranteed quality and quality. Employment Analysts occupies a strategic position because it is the foundation of staffing management services. Therefore a strategy is needed to improve competency and professionalism of the staffing analyst position to support the process of staffing services properly and satisfactorily. And the strategies that are intended include: Increasing continuous performance, creating effective communication patterns, creating innovative ideas in the field of staffing, following the certification program for Employee Analysts, carrying out professional career development for Staff Analysts. Keywords : Competence, Professionalism